Analysis of Strategic Planning for Enhancing the Capacity of Health Human Resources at Community Health Centers (Puskesmas) in Minahasa Regency - Olviane I. Rattu; Jeffry Sony Junus Lengkong; Joulanda A M Rawis; Harol R. Lumapow; Ruth Umbase (JR Education, 2026)
The development of health human resources (HHR) is a critical determinant in improving the quality and effectiveness of primary healthcare services, particularly in community health centers (Puskesmas). In the context of decentralization and regional autonomy, local governments are required to manage health workforce planning strategically to ensure adequate availability, equitable distribution, and appropriate competencies of healthcare personnel. However, many regions in Indonesia continue to face persistent challenges, including workforce shortages, uneven distribution across geographical areas, and limited capacity development programs. This study aims to analyze the strategic planning process for enhancing the capacity of health human resources at community health centers in Minahasa Regency. Specifically, the study examines four key stages of planning: preparation, situational analysis, problem formulation, and the development of activity plans (Rencana Usulan Kegiatan/RUK). A qualitative approach with a case study design was employed to explore the complexity of planning processes within real organizational settings. Data were collected through in-depth interviews, observations, and document analysis involving key stakeholders, including health office officials, Puskesmas managers, healthcare workers, and planning personnel. Data analysis was conducted using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The findings reveal that although strategic planning processes have been formally implemented in accordance with national guidelines, their execution remains suboptimal. Key issues identified include insufficient availability of health personnel, lack of accurate and updated workforce data, weak integration between planning and budgeting, limited capacity of planning staff, and inconsistencies between Puskesmas-level planning and district-level policies. Furthermore, the study highlights that educational management plays a crucial role in strengthening health workforce planning through continuous professional development, competency-based training, and systematic evaluation. The integration of management functions, planning, organizing, actuating, and controlling (POAC), is essential to ensure sustainable human resource development in primary healthcare settings. This study concludes that strengthening strategic planning for health human resources requires a comprehensive approach that integrates workload-based planning methods, capacity building for planners, improved data systems, and stronger policy support. It recommends the adoption of competency-based planning frameworks, enhanced intersectoral collaboration, and the institutionalization of continuous education programs to improve the quality of health services at Puskesmas.